Characteristics of polypropylene-based antistatic bio-nano composites reinforced with mono-diacylglycerols and cellulose nanocrystals - Dwi Setyaningsih; Muhammad Syukur Sarfat; Farah Fahma; Nastiti Siswi Indrasti (Materials Research Express, 2024)
Polypropylene (PP) is known as a polymer without antistatic properties that is susceptible to the use of high temperatures. Therefore, to improve the thermal and antistatic properties of PP, it is necessary to modify PP to antistatic bio-nanocomposites with mono-diacylglycerols (M-DAG) as an antistatic agent and cellulose nanocrystals (CNC) as a reinforcement. This research aimed to characterize the electrical resistivity and thermal properties of PP-based antistatic bio-nanocomposites reinforced with M-DAG and CNC at different concentrations of CNC (0%–5%), and 2% of M- DAG, compared to pure PP. The results showed that the addition of 2% CNC (AS-BNC-2) gave the melting temperature of 125.0 °C, which was higher than pure PP of 118.3 °C. The thermal stability of the antistatic bio-nano composites with 3% CNC (AS-BNC-3) was 457.10 °C, which was higher than pure PP of 441.56 °C. The electrical resistivity of the antistatic bio-nano composites from all treatments was still in the range of the antistatic category of 10 ^10 –10 ^12 Ω/sq. The melting temperature and thermal stability of bio-nano composites were higher than those of pure PP and they have antistatic properties. This indicates the potential application of these materials in the electronics devices and packaging industries.